ANALYSIS OF GOVERNMENT COMMUNICATION STRATEGY IN IMPLEMENTING COVID 19 VACCINATION IN JAYAWIJAYA DISTRICT: HARROLD D. LASSWELL'S PERSPECTIVE - Misrah, Irmayani; Pratama, Wahyu Adi; Ismail, Rudihartono (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2024)
The government issued Presidential Regulation Number 99 of 2020 concerning Vaccine Procurement and Implementation of Vaccination in the Context of Handling the Covid 19 Pandemic. From this regulation, the Ministry of Health of the Republic of Indonesia created a communication strategy to increase the trust and participation of health workers and the public in the free vaccination program in stages. This study aims to explain the government's communication strategy in implementing the COVID-19 vaccination in Jayawijaya Regency from the perspective of Harrold D. Lasswell. The research method uses a qualitative approach. The theory used to analyze the communication strategy is the theory of Harrol D. Lasswell. The results of the study showed that the Jayawijaya Regency Health Office's communication strategy was by the phenomena that existed in society, but the implementation and the target of vaccination were not optimal. This can be seen from the results of the study which showed that Who? (who/communicator) in the socialization of vaccination, there are still figures who reject or do not support the vaccination, Say What? (Message) The amount of irresponsible information related to vaccination is spreading among the community, and there is a lack of correct information related to vaccination.